High-Performing Young Musicians’ Playing-Related Pain. Results of a Large-Scale Study - Gembris, Heiner; Menze, Jonas; Heye, Andreas; Bullerjahn, Claudia (Frontiers in Psychology, 2020)
The present study examines the prevalence, localization, frequency, and intensity of playing-related pain (PRP) in a sample of high-performing young musicians. We also address coping behavior and communication about PRP between young musicians, teachers, parents, and other people, such as friends. The aim is to provide information on PRP among high-performing musicians in childhood and adolescence, which can serve as a basis for music education, practice, and prevention in the context of instrumental teaching and musicians’ health. The study is part of a large-scale study (N = 1,143) with highly musically gifted participants (age 9-24 years; M = 15; SD = 2.1, female = 62%) at the national level of the “Jugend musiziert” (youth making music) contest. For data analyses, we used descriptive statistics, correlations, Chi2 tests, principal component analysis, a Kruskal Wallis H test, and multivariate regression. About three-quarters (76%) of the surveyed participants stated that they had experienced pain during or after playing their instrument. Female musicians were significantly more frequently affected (79%) than male musicians (71%). With increasing age, the prevalence of PRP rises from 71 percent (9-13 years) to 85 percent (18-24 years). Regarding localization of pain, results are in line with many other studies with musculoskeletal problems the most common. Furthermore, data show a clear relationship between the duration of practice and the prevalence of PRP. Our study found averages of 7:18 hours/week, whereas mean values of the duration of practice vary considerably between different instruments. The variance in practice duration is very large within the different instruments. Thus, when researching PRP, it is necessary to consider both the differences between different groups of instruments in the average duration of practice as well as the very large inter-individual variation in the duration of practice within a given instrument group. While just over half of the young musicians (56%) felt they had been taken seriously, 32 percent felt that their complaints were not completely taken seriously, and 12 percent did not feel taken seriously at all. Therefore, it is necessary to improve communication and information about PRP to prevent PRP and counteract existing complaints.